Convergence in the Nigerian Communications Sector: A Case for Legal and Regulatory Reforms - Mgbeokwere, Chineye Joy (ABUAD Private and Business Law Journal, 2018)
The reform in the communication sectors as a result of liberalization and digital technology in the hitherto analog sector has brought in its wake a new phenomenon called Communication Convergence. Digital technology in the communications sector has converged the distinct communication subsectors into one. This has caused overlap of regulatory functions among the distinct regulators, collision in the regulatory bodies, ineffective or over regulation, inefficient use and allocation of scare resources and making most provisions in the enabling Act obsolete. This poses some legal and regulatory challenges to the regulators. In this regard, the paper using the doctrinal methodology analysed the Nigerian Communications Act 2003, other relevant legislations, policies, case law and literatures on communications. The study finds out that the existing Nigerian Communications Act 2003 is inadequate to engender an efficient and effective regulation of the sector in an ICT convergent era as the Act made provisions for only telecommunications and its specific regulator. It recommended that, the various policies and laws in the communicationsubsectors in Nigeria should be reviewed,harmonised and a converged law enacted. It concludes that the Nigerian Communications law should be reviewed constantly and made more flexible because of the evolving nature of convergence.